Not everything that connects is a network - and Hearn, Simon; Mendizabal, Enrique (ODI, 2011)
In the public policy context, networks have been predominant factors in policy formulation, innovation and global governance. While not a new phenomenon in the development landscape, networks are becoming increasingly prevalent. Donors, for example, are turning to networks to deliver aid interventions, NGOs are working through networks for collective advocacy and researchers collaborate across networks for greater policy influence. But are networks always the most appropriate vehicle? Where they are appropriate, how can we make the best use of them? This Background Note argues for a more rigorous understanding of their nature, particularly their value (and costs), and presents a revised Network Functions Approach as a model for rationalised investment in networks.